Citrus limon Peel Essential Oil–Induced Type IV Hypersensitivity Reaction - Mahdani FY; Parmadiati AE; Ernawati DS; Husain H; Ekaperdana SAP; Rachmaningayu U; Hadi P; Hendarti HT; Surboyo MDC (Dove Medical Press, 2020)
Fatma Yasmin Mahdani,1 Adiastuti Endah Parmadiati,1 Diah Savitri Ernawati,1 Hasrul Husain,2 Sekar Alifa Putri Ekaperdana,3 Ulyasari Rachmaningayu,3 Priyo Hadi,1 Hening Tuti Hendarti,1 Meircurius Dwi Condro Surboyo1 1Department of Oral Medicine, Faculty of Dental Medicine, Universitas Airlangga, Surabaya 60132, Indonesia; 2Oral Medicine Specialist Program, Faculty of Dental Medicine, Universitas Airlangga, Surabaya 60132, Indonesia; 3Bachelor Program, Faculty of Dental Medicine, Universitas Airlangga, Surabaya 60132, IndonesiaCorrespondence: Fatma Yasmin MahdaniDepartment of Oral Medicine, Faculty of Dental Medicine, Campus A Universitas Airlangga, 47 Jalan Prof Dr Moestopo, Surabaya 60132, East Java–Indonesia, Tel +62-31-503-0255Fax +6231 5020256Email fatmayasminmahdani@fkg.unair.ac.idBackground: Several studies have shown anti-inflammatory, anti-microbial, antifungal, and antioxidant effects from Citrus limon–peel essential oil (Cl-PEO). Cl-PEO can be developed as topical drugs for oral ulceration because of its potential active components. There have been no studies on the topical application of Cl-PEO inducing type IV hypersensitivity reaction.Purpose: To investigate the potential of Cl-PEO from Batu City to induce type IV hypersensitivity reactions based on clinical changes, lymphocytes, macrophages, IFNγ, andIL10 expression.Methods: This study was adapted from a guinea pig maximization-test method in Indonesia and the guidance of ISO 10,993-10:2010, and conducted on 20 guinea pigs (Cavia cobaya) divided into a control group and a treatment group. The treatment group was given Cl-PEO and the control group CMC-Na. Clinical changes were observed, then tissue specimens taken for hematoxylin–eosin and immunohistochemistry staining.Results: There were no clinical changes after exposure. Lymphocyte and macrophage numbers and IFNγ and IL10 expression increased in the treatment group compared to the control group (p=0).Conclusion: Cl-PEO can induce type IV hypersensitivity reactions in guinea pigs based on cellular and molecular cytokines, but there are no clinical changes after topical application.Keywords: Citrus limon, essential oil, type IV hypersensitivity, macrophages, lymphocytes, interferon gamma, interleukin 10